ONLINE LEARNING STRATEGIES IN PAI SUBJECTS DURING THE COVID-19 PANDEMIC IN CLASS VIII U2 SMP GUSTI WIJAYA SUNGGAL - Fitri Amaliyah Batubara; Nurhalima Tambunan; Sri Rindu Wina (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine online learning strategies in Islamic religious education during the Covid-19 pandemic in class VIII U2 of Gusti Wijaya Sunggal Private Middle School and to determine the supporting and inhibiting factors of the online learning process during the Covid 19 pandemic at Gusti Wijaya Sunggal Private Middle School. The form of this research is qualitative research with data sources used are primary and secondary data sources. The data obtained is then analyzed continuously by means of data reduction, data display, data verification, and data validity testing (triangulation). The results of the study show that the online learning strategy of the Gusti Wijaya Sunggal Private Middle School in Islamic religious education subjects utilizes technology and social media while maintaining good cooperation with parents through the WhatsApp group during online learning with more emphasis on character education, life skills ( life skills), as well as good morals.